Reconsidering Liberal Human Rights: Epistemological and Ethical Criticism in the Perspective of Al-Ghazali's Thought - Bayu Asep Saputra; Siti Suniah (Published by Institut Teknologi Pendidikan Indonesia, 2026)
This study aims to re-examine the epistemological foundations and ethical dimensions of liberal human rights through the perspective of Al-Ghazali. Liberal human rights, which are rooted in secular rationalism, place individual freedom as the central principle in determining moral values and human conduct. However, this paradigm is often criticized for neglecting transcendental dimensions and creating space for moral relativism. This research employs a qualitative approach using library research methods. The data were collected from the major works of Al-Ghazali, scholarly books, academic journals, and relevant literature discussing liberal philosophy and modern human rights discourse. The analysis was conducted using descriptive-analytical and comparative-critical methods to examine the differences between liberal human rights and Al-Ghazali’s ethical and epistemological framework, particularly regarding freedom, morality, and public welfare. The findings reveal that the epistemology of liberal human rights, which relies heavily on human reason, has limitations in establishing absolute moral standards. According to Al-Ghazali, true knowledge should integrate reason, revelation, and spiritual intuition (kashf). Furthermore, human freedom cannot be separated from moral responsibility and the divine purpose of humanity as both servant and steward of God on earth. Al-Ghazali’s concepts of tazkiyat al-nafs (purification of the soul) and maqasid al-shariah offer an alternative framework that balances individual rights with social welfare and spiritual values. Therefore, Al-Ghazali’s critique of liberal human rights remains highly relevant in addressing contemporary moral and spiritual crises while providing a more holistic, value-oriented, and spiritually grounded understanding of human right